The impact of the COVID-19 related lockdowns on air quality. Issue 1 (July 2020) - Bogomolova, Arina; Balk, Igor; Polkovnikova, Natalia; Ivaschenko, Natalya
Abstract: Lockdowns imposed on population around the world due to COVID-19 provided unique opportunity to study impact of humankind of the environment. In this paper we discuss the magnitude of the anthropogenic impact on climate change, and in particular on-air pollution, since these two phenomena are interconnected. We used daily data on air pollution in several large cities, where serious restrictive measures were introduced in the context of a pandemic for a large number of citizens. The study period includes several months of 2020, including the moment of quarantine introduction, as well as the same period of 2019. Thus, we will check whether the impact of human activities on climate change is significant.